Metabolic Changes in Peripheral Blood Mononuclear Cells Isolated From Patients With End Stage Renal Disease - Altintas, Mehmet M.; DiBartolo, Salvatore; Tadros, Lana; Samelko, Beata; Wasse, Haimanot (Frontiers in Endocrinology, 2021)
As numerous complex pathologies stem from cellular energy dysfunction, we aimed to elucidate mitochondrial function and associated stress pathologies in kidney disease in a cohort of hemodialysis patients with end-stage kidney disease (ESKD). The bioenergetics study was conducted using peripheral blood mononuclear cells (PBMCs) of ESKD patients (n=29) and healthy controls (no ESKD, n=10). PBMCs were isolated from whole blood and seeded into assay plates to detect changes in oxidative phosphorylation and glycolysis. The bioenergetics analysis (i.e., mitochondrial stress test) was performed using Seahorse XFe24 flux analyzer. We observed significant reduction in mitochondrial respiration in patient PBMCs in terms of fundamental bioenergetics parameters such as basal respiration, ATP turnover, maximal respiration and spare respiratory capacity. These findings were correlated with the expression levels of proteins coordinating cellular energy status and regulating mitochondrial dynamics. Our data demonstrates an association between mitochondrial oxygen consumption of PBMCs and ESKD. AMPK activity, its downstream effector PGC-1 and mitochondrial fission/fusion proteins are partially responsible for the decrease in oxidative phosphorylation of PBMCs isolated from ESKD patients. We propose a link between mitochondrial dysfunction and ESKD and a role for mitochondria as a potential site for therapeutic interventions.